US POLICY AND DEMOCRACY CHALLENGES IN LATIN AMERICA AND THE CARIBBEAN - Tkach (Ткач Анатолій Олегович), Anatoly (Politology bulletin, 2019)
Formulation of the problem: In the article management problems are examined Geographic proximity has ensured strong linkages between the United States and Latin America and the Caribbean, based on diverse U.S. interests, including economic, political, and securityт concerns. The United States is a major trading partner and the largest source of foreign investment for many countries in the region, with free-trade agreements enhancing economic linkages with 11 countries.Purpose of the research: The region is a large source of U.S. immigration, both legal and illegal; proximity and economic and security conditions are major factors driving migration. Curbing the flow of illicit drugs has been a key component of U.S. relations with the region for more than three decades and currently involves close security cooperation with Mexico, Central America, and the Caribbean. U.S. support for democracy and human rights in the region has been long-standing, with particular current focus on Cuba, Nicaragua, and Venezuela.The article analyzes the priorities of Administration of President Trump ordered U.S. withdrawal from the proposed Trans-Pacific Partnership trade agreement, which would have increased U.S. economic linkages with Mexico, Chile, and Peru. President Trump criticized the North American Free Trade Agreement (NAFTA) with Mexico and Canada as unfair, warned that the United States might withdraw, and initiated renegotiations; ultimately, the three countries agreed to a United States-Mexico-Canada Agreement in late September 2018. The proposed agreement, which requires congressional approval, largely leaves NAFTA intact but includes some updates and changes, especially to the dairy and auto industries. Administration actions on immigration have caused concern in the region, including efforts to end the deportation relief program known as Deferred Action for Childhood Arrivals (DACA) and Temporary Protected Status (TPS) designations for Nicaragua, Haiti, El Salvador, and Honduras. President Trump unveiled a new policy in 2017 toward Cuba partially rolling back U.S. efforts to normalize relations and imposing new sanctions.

Метою дослідження є визначення складових відносин США та країн Латинської Америки, демократичного управління в країнах Латинської Америки за умов авторитарних та демократичних режимів. Автор аналізує авторитарні стратегії економічного та політичного управління. Особлива увага приділена розвитку відносин у контексті політичних та економічних наслідків авторитаризму.Результати та висновки Географічна наближеність забезпечила міцні зв’язки між США та країнами Латинської Америки на основі різноманітних інтересів США, включаючи економічні, політичні та проблеми безпеки. США є основним торговим партнером і найбільшим джерелом іноземних інвестицій для багатьох країн регіону, з угодами про вільну торгівлю, які посилюють економічні зв’язки з 11 країнами. Регіон є джерелом імміграції США, як легальної, так і незаконної; близькість та економічні та безпекові умови є основними факторами, що сприяють міграції. Стримування потоку незаконних наркотиків є ключовим компонентом відносин США з регіоном протягом більше трьох десятиліть і в даний час передбачає тісне співробітництво з Мексикою, Центральною Америкою та Карибським регіоном. США підтримують демократію та права людини в регіоні давно, з особливою увагою до Куби, Нікарагуа та Венесуели. Відповідно до Адміністрації Трампа, перспективи відносин США з регіоном змінилися. Адміністрація запропонувала глибоке скорочення допомоги регіону. Щодо торгівлі, президент Трамп наказав США вийти з запропонованої торговельної угоди TransPacific Partnership, яка збільшила б економічні зв’язки США з Мексикою, Чилі та Перу. Президент Трамп критикував Північноамериканську угоду про вільну торгівлю (НАФТА) з Мексикою та Канадою, як несправедливих, попередив, що США можуть вийти, і розпочали переговори; три країни погодилися на угоду США-Мексика-Канада наприкінці вересня 2018 р.
ПОЛІТИКА США ТА ВИКЛИКИ ДЕМОКРАТІЇ В ЛАТИНСЬКІЙ АМЕРИЦІ ТА КАРИБСЬКОМУ БАСЕЙНІ
Keywords: demokracy; political process; global events; associated construction; еffective source; government; політичний режим; політичний процес; ґлобальні події; економічна криза; інтеграція